A mediação e a conciliação na ótica do novo CPC: a importância da utilização dos meios “alternativos” de solução de conflito e o sistema multiportas para o acesso à justiça - Oliveira, Lázaro Henrique de Paula (2018)
The present work seeks to analyze the innovations of the New Code of Civil Procedure, regarding the use of the multi-door courthouse, which starts from the premise that for each concrete case there may be more than one way to achieve a solution favorable to the parties, which is not always will be the judiciary. We also consider the importance of the stimulus given by the legislator to the use of mediation and conciliation as access to justice, breaking the paradigm that the judiciary would be the only door capable of solving a given conflict. Finally, a brief analysis was made of the "compulsory" conciliation and mediation hearing provided for in article 334, based on some judgments given in some State Courts of the country.